IMPLEMENTASI PROGRAM PERTEMUAN PENINGKATAN KEMAMPUAN KELUARGA (P2K2) DI KECAMATAN SUKARAJA KABUPATEN SELUMA - Linda Triana; Aries Munandar; Lisa Adhrianti; Tamrin Bangsu; Yunisiliah Yunisiliah (Smart Education, 2025)
Abstract: The Family Capacity Building Meeting (P2K2) program aims to change the behavior of beneficiary families (KPM) of the Family Hope Program (PKH) to be more independent in managing finances, parenting, education, social welfare, child protection, and family health. However, although many KPM have graduated, the number of new recipients continues to grow. This study analyzes the implementation of P2K2 in Sukaraja District, Seluma Regency, using a descriptive qualitative method with observation, interviews, and documentation studies. Informants were selected by purposive sampling, consisting of 12 people, including KPM, the Social Service, the sub-district government, and PKH assistants. The results of the study showed that the implementation of P2K2 was in accordance with Permensos Number 1 of 2018 and Number 10 of 2017. However, its effectiveness was still low. Socialization was less than optimal because the material was difficult for KPM to absorb. Implementation was more of a formality, without real application in everyday life. Monitoring and evaluation were also limited, only carried out once a month or when conditions were urgent. In conclusion, although the program is running according to regulations, its effectiveness needs to be improved with a more flexible approach, intensive monitoring, and easier-to-understand materials to truly encourage KPM independence towards graduation from PKH.Â Keyword: implementation, program, family capacity building meeting.Â Abstrak: Program Pertemuan Peningkatan Kemampuan Keluarga (P2K2) bertujuan mengubah perilaku keluarga penerima manfaat (KPM) Program Keluarga Harapan (PKH) agar lebih mandiri dalam pengelolaan keuangan, pengasuhan, pendidikan, kesejahteraan sosial, perlindungan anak, dan kesehatan keluarga. Namun, meskipun banyak KPM telah graduasi, jumlah penerima baru terus bertambah. Penelitian ini menganalisis implementasi P2K2 di Kecamatan Sukaraja, Kabupaten Seluma, menggunakan metode kualitatif deskriptif dengan observasi, wawancara, dan studi dokumentasi. Informan dipilih secara purposive sampling, terdiri dari 12 orang, termasuk KPM, Dinas Sosial, pemerintah kecamatan, serta pendamping PKH. Hasil penelitian menunjukkan implementasi P2K2 telah sesuai dengan Permensos Nomor 1 Tahun 2018 dan Nomor 10 Tahun 2017. Namun, efektivitasnya masih rendah. Sosialisasi kurang optimal karena materi sulit diserap KPM. Implementasi lebih bersifat formalitas, tanpa penerapan nyata dalam kehidupan sehari-hari. Monitoring dan evaluasi pun terbatas, hanya dilakukan sebulan sekali atau saat kondisi mendesak. Kesimpulannya, meskipun program berjalan sesuai regulasi, efektivitasnya perlu ditingkatkan dengan pendekatan lebih fleksibel, monitoring intensif, serta materi yang lebih mudah dipahami agar benar-benar mendorong kemandirian KPM menuju graduasi dari PKH.Â Kata kunci: implementasi, program, pertemuan peningkatan kemampuan keluarga.